Taxonomic review of the tree snail genus Amphidromus Albers, 1850 (Pulmonata: Camaenidae) in Laos, with the description of two new species - Inkhavilay, Khamla; Sutcharit, Chirasak; Panha, Somsak (European Journal of Taxonomy, 2017)
The land snail genus Amphidromus Albers, 1850 and its subgenus Syndromus Pilsbry, 1900 (family Camaenidae) in Laos are revised. Fourteen species from various habitats of deciduous forest and limestone areas throughout Laos are confirmed. The classification is revised and discussed, based on material examined from Laos, Cambodia, Vietnam and Thailand and after comparison with the type specimens in many museums. Two new species, A. (Amphidromus) syndromoideus Inkhavilay & Panha sp. nov., from central Laos, and A. (Syndromus) xiengkhaungensis Inkhavilay & Panha sp. nov., from northern Laos, are described and discussed.